Power allocation for multisource, multidestination cooperative vehicular networks under an outage probability constraint. Issue 3 (22nd April 2019) - Zhou, Di; Qiu, Bin; Chen, Yuanfang; Xiao, Hailin; Alam, Muhammad
Abstract: In multisource, multidestination vehicular networks, vehicles equipped with wireless communication devices are capable of sharing data with each other as well as relaying data using roadside infrastructures. Therefore, low‐power wireless communications play a critical role in improving the performance of transportation systems. To substantially reduce the power consumption of the transportation systems, a new power allocation strategy operating with an amplify‐and‐forward and hybrid decode‐amplify‐forward (AF‐HDAF) protocol is proposed and analyzed. The cooperative manners of the employed relay nodes in the AF‐HDAF strategy are manipulated, relying on the smartly designed forward strategies of the cooperative nodes. Furthermore, based on an outage probability constraint, the optimal power allocation that minimizes the sum power consumption is investigated. Numerical results confirm the validity of the proposed theoretical analysis, showing that the performance of the proposed power allocation scheme can be substantially improved by implementing the proposed AF‐HDAF protocol. Abstract : amplify‐and‐forward and hybrid decode‐amplify‐forward (AF‐HDAF); power allocation; vehicular communication; cooperative vehicular network; outage probability; multisource; multidestination